Facial dermatosis papulosa nigra, a risk for the development of pterygium and myopia: a descriptive cross-sectional study in Ghana - Du-Bois Asante; Korantema M. Tsegah; Ebenezer Afrifa-Yamoah; Samuel Kyei; Dunyah J. Dzidzor; Reindolf Anokye (AOSIS, 2022)
Background. Dermatosis papulosa nigra (DPN) affects sun-exposed areas such as the face, neck, and trunk. The prevalence of pterygium and myopia in DPN patients in Ghana has not been studied. In this study, we examined the risk and protective factors for pterygium and myopia in DPN patients. Materials and Methods. The study involved 100 participants with facial DPN. A standard ophthalmic exam was performed using a portable slit lamp and a 3.5X magnified loop. Participants completed a closed-ended questionnaire. Logistic regression was used to summarize the level of association between DPN, myopia, and pterygium, as well as demographic factors (gender, age, occupation, family history of lesion and skin complexion). Results. 70% and 84% of participants had pterygium and myopia. Age, gender, complexion, and sun exposure were associated with pterygium and myopia (p 0.05). Higher grade of pterygium and myopia were prevalent in the aged population. Both univariate and multivariable models highlighted that increasing age and sun exposure (outdoor) were risk factors for developing higher grade of pterygium and myopia in the DPN participants, while light skin color and male gender were respectively identified as protective factors. Conclusions. Our study is the first to examine pterygium and myopia in facial DPN patients. Most Ghanaians with facial DPN are at risk for developing pterygium and myopia.